The impact of cash flow statement on firm value in indonesia - Itan, Iskandar; Riana, Wiwy (FORUM EKONOMI, 2021)
This study aimed to determine the impact of cash flow statement on firm value in Indonesia companies that listed on the Indonesia Stock Exchange. The total data used as the sample was 1,236 data including all sectors except financial sectors for the period 2015 to 2019. The fixed effect model was chosen as the best model to analyze panel data. Furthermore, Eviews 10 application was also to help the process of regression. The results of this study showed that the operating cash flow ratio had a positive significant effect on firm value. Meanwhile, the investing cash flow ratio and financing cash flow ratio had a negative significant effect on firm value. In addition, the results also indicated that operating dummy and investing dummy had no effect on firm value. Besides, the financing dummy was the same as financing cash flow ratio that significantly affected the firm value. Furthermore, both managers’ holding ratio and board size revealed a significant relationship to the firm value, while the independent director dummy showed a positive significant effect on firm value.